1989
DOI: 10.1111/j.1600-0447.1989.tb05252.x
|View full text |Cite
|
Sign up to set email alerts
|

The stress upon rescures involved in an oil rig disaster. “Alexander L. Kielland” 1980

Abstract: Nine months post‐disaster, 134 rescuers involved in an off‐shore oil rig disaster were investigated by using a structured self report questionnaire to chart their experience of coping with disaster impact stressors and their mental and physical health 9 months after the disaster. Of the 134 rescuers, 24 were categorized as professional rescuers, 101 as non‐professionals and 9 could not be classified. Of the 212 victims, all oil rig workers, 89 (42%) were rescued. Seventy‐six percent of the rescuers reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
2
17

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(98 citation statements)
references
References 8 publications
3
76
2
17
Order By: Relevance
“…Après l'un des pires désastres marins de l'histoire, un groupe de sauveteurs a dû retirer des décombres d'une plateforme pétrolière un grand nombre de cadavres en décomposition, ce qui constitue une expérience traumatique très intense. Suite à cette expé-rience, Ersland et al (1989) ont observé que les sauveteurs aguerris avaient moins de troubles mentaux (4,3%), que les sauveteurs avec peu (33,3%) ou pas d'expérience (26,2%). Dans la même veine, Hytten et al (1989) ont constaté qu'à la suite d'un incendie, les pompiers volontaires sans expérience avaient un score moyen de détresse post-traumatique plus élevé que les pompiers volontaires avec expérience.…”
Section: Epstein Et V Inoculation Graduelle Au Stressunclassified
“…Après l'un des pires désastres marins de l'histoire, un groupe de sauveteurs a dû retirer des décombres d'une plateforme pétrolière un grand nombre de cadavres en décomposition, ce qui constitue une expérience traumatique très intense. Suite à cette expé-rience, Ersland et al (1989) ont observé que les sauveteurs aguerris avaient moins de troubles mentaux (4,3%), que les sauveteurs avec peu (33,3%) ou pas d'expérience (26,2%). Dans la même veine, Hytten et al (1989) ont constaté qu'à la suite d'un incendie, les pompiers volontaires sans expérience avaient un score moyen de détresse post-traumatique plus élevé que les pompiers volontaires avec expérience.…”
Section: Epstein Et V Inoculation Graduelle Au Stressunclassified
“…This figure must be judged with caution as the instrument has not been calibrated for diagnosis in this context, but it seems uncharacteristically low in comparison to international research studies, which estimate prevalence to be between 15% -64% (Corneil, 1993;Ersland et al, 1989;McFarlane, 1988;Raphael & Wilson, 1993;Ravenscroft, 1993;Robinson, 1994). Mollica et al (1991:21) make the point that "...the ability of the instrument (Harvard Trauma Questionnaire) to detect people who have the disease is well covered, since the cut-off score was set at a relatively high level.…”
Section: The Prevalence Level Of Ptsd Symptoms In Emergency Service Amentioning
confidence: 99%
“…They found that 10% had experienced the incident as stressful, to the extent of interfering with their job performance. Ersland, Weisaeth & Sund (1989) studied 134 rescuers following an oil rig disaster in Norway. They found that 52% to 64% of the rescuers were suffering from discouragement, restlessness, uncertainty, anxiety and irritation.…”
Section: Emergency Service Ambulance Personnel (Esap) and Traumamentioning
confidence: 99%
“…En certaines situations, ils risquent également d'encourir des risques à leur santé physique similaires à ceux qu'affrontent les individus auxquels ils portent assistance ou secours (Ersland et al, 1989 ;Laube-Morgan, 1992 ;Marmar et al, 1996). On constate toutefois de fortes différences dans les réactions au stress vécu chez les intervenants et dans les types de facteurs qui les influencent -formation, éducation, personnalité associée au type de travail, etc.…”
Section: Introduction Retour à La Table Des Matièresunclassified